Cyp‐Rus investment flows to central and Eastern Europe ‐ Russia's direct and indirect investments via Cyprus to Cee - Pelto, Elina; Vahtra, Peeter; Liuhto, Kari (Journal of Business Economics and Management, 2004)
This paper deals with Russian investments to ten Eastern European EU candidate countries. Eastern European countries are an important destination for Russian OFDI, and the share of Russia in many CEEC's inward FDI stock is substantial. Russian investments to these countries are mostly connected to the internationalisation of Russian energy sector. Russian oil and gas giants have been actively investing to almost all eastern EU candidate countries. However, OFDI constitutes only a small part of Russian capital abroad, as it covers merely 10 % of the Russian capital flight. Cyprus has been an important landing place for Russian capital flight and is currently the biggest direct investor to Russian economy. Also the investment flow from (or via) Cyprus to other Eastern European countries is relatively big. Significant share of these Cypriot investments are considered to be of Russian origin. This paper tries to anticipate the effects of the legislative changes, due to Cyprus's EU accession in 2004, on the role of Cypriot offshore sector as a landing place for Russian capital.First Published Online: 14 Oct 2010